IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma. Issue 3 (30th March 2017) - Baraldo, Simonetta; Papi, Alberto; Saetta, Marina; Contoli, Marco
We read with interest the paper by Bergauer et al. [1] on innate immune responses to viral infection in paediatric asthma. The paper confirms previous reports on impaired interferon responses in stable asthma [2–4], but describes a hyperactive interferon production during asthma exacerbations associated with rhinovirus infection. The authors conclude that, despite impaired immune condition at stable state, the ability to upregulate type I interferons during the acute phase is preserved in asthmatic children. However, what is lacking from this study is the information on interferon production during acute rhinovirus infection in an age-matched group of non-asthmatics. Thus, how can it be conclusively excluded that the production of interferon is impaired during the rhinovirus-induced acute phase of asthma in the absence of such a comparative control group? A study which examined nasal washes of children during acute episodes of wheezing or rhinitis, reported lower levels of IFN-λ in children with wheezing than in those with acute rhinitis, even if the differences were not statistically significant [5]. The fact that asthmatic patients, once infected, have more severe manifestations of the infectious diseases [6] could possibly suggest an impaired response also in the acute phase, but conclusive data are lacking. Does impaired interferon production in stable asthma also occur during rhinovirus-induced acute asthma attacks? http://ow.ly/kgVe309GazS